Clair-obscur: poesie - Cocteau, Jean, 1889-1963 (Le Rocher, 2003)
"Poems, your perfumes, your shapes, your colors. Serves for other purposes than I imagine[...] Poems, cruel flowers, together I put you away. Traps haloed with dangerous rays" Published in 1954, Clair- Obscur brings together a hundred poems. This book sings of the poet's disillusion in the face of the modern world and his revolt in the face of the otherness of time. Faithful to his genius, Cocteau combines humor and seriousness. He also pays tribute to the painters and writers who inspired him and to Spain, a country that was dear to him. Jean Cocteau, born in 1889 and died in 1963, is one of the greatest French poets of the 20th century, a multi-talented artist, novelist, designer, painter, playwright and filmmaker. He was elected to the Académie française in 1955. Letter-preface from Gaston Bachelard